2014
DOI: 10.4041/kjod.2014.44.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of polyurethane dental arch models fabricated using a three-dimensional subtractive rapid prototyping method with an intraoral scanning technique

Abstract: ObjectiveThis study aimed to evaluate the accuracy and precision of polyurethane (PUT) dental arch models fabricated using a three-dimensional (3D) subtractive rapid prototyping (RP) method with an intraoral scanning technique by comparing linear measurements obtained from PUT models and conventional plaster models.MethodsTen plaster models were duplicated using a selected standard master model and conventional impression, and 10 PUT models were duplicated using the 3D subtractive RP technique with an oral sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 22 publications
1
22
0
4
Order By: Relevance
“…Linear measurements are frequently used to measure the accuracy of dental replica models, but have limited number of measuring points . Furthermore, since the positions of measuring points on the surface affect the accuracy, the rough surface of AM models hinders the identification of reference markers on it . In this study, 3D analysis software was used to reduce this type of error by using multiple overlapping points and to increase the accuracy of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Linear measurements are frequently used to measure the accuracy of dental replica models, but have limited number of measuring points . Furthermore, since the positions of measuring points on the surface affect the accuracy, the rough surface of AM models hinders the identification of reference markers on it . In this study, 3D analysis software was used to reduce this type of error by using multiple overlapping points and to increase the accuracy of measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, natural tooth-shaped models manually prepared by the researcher or full-arch dentiforms were used to test the accuracy and precision of intraoral scanners 6,9,14,20,23,24) . Alongside the development of various types of intraoral scanners, multiple studies have been conducted on their accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the casts generated by CAI techniques, studies have examined both virtual and real casts. Virtual casts have been extensively studied in the orthodontic literature where storage of pre‐ and post‐treatment casts needed for treatment planning and case evaluation is imperative . Storage of these casts requires much space in a busy orthodontic practice.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative analysis suggests that the dimensional accuracy of the casts was within one‐third of a millimeter. A comparison of RP with milling suggests that the former results in a more accurate cast for studies in which an actual cast was produced . Studies in the prosthodontic literature have reported trueness in the range of 30 to 50 μm for actual casts.…”
Section: Discussionmentioning
confidence: 99%